2010
DOI: 10.1186/1752-1947-4-157
|View full text |Cite
|
Sign up to set email alerts
|

An unusual foreign body as cause of chronic sinusitis: a case report

Abstract: IntroductionThe presence of a foreign body in the nose is a relatively uncommon occurrence. Many unusual foreign bodies in the nose have been reported in the literature, but no case of a nasal packing occurring as a foreign body in the nasal cavity for a prolonged time has been found.Case presentationWe describe a unique case of the largest foreign body left in situ in the nasal cavity for over 10 years. Our patient was a 71-year-old Caucasian man with diabetes. Because of this, he was at high risk of developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…11 Sinus malignancy through chronic stimulation of carcinogen from foreign bodies has also been reported. [11][12][13][14][15] Uniqueness of the present case is in the fact that past history of facial trauma by a stone 30 years back was present which patient had also forgotten and patient presented with a history of only 15 days. History, examination and radiological findings suggested that the case may be of carcinoma maxilla.…”
Section: Discussionmentioning
confidence: 97%
“…11 Sinus malignancy through chronic stimulation of carcinogen from foreign bodies has also been reported. [11][12][13][14][15] Uniqueness of the present case is in the fact that past history of facial trauma by a stone 30 years back was present which patient had also forgotten and patient presented with a history of only 15 days. History, examination and radiological findings suggested that the case may be of carcinoma maxilla.…”
Section: Discussionmentioning
confidence: 97%
“…Although, it had not caused any adverse effects in this patient, FB in the nose may cause nasal obstruction, rhinosinusitis, tissue necrosis and epistaxis. [4][5][6] These complications may occur when the FB causes swelling of the nasal mucosa. There are many documented risks of using NGT.…”
Section: Discussionmentioning
confidence: 98%
“…The nose is among the most common sites for aerodigestive foreign bodies 7 , 8 . Cases are heavily skewed toward pediatric patients, while incidents among adults are generally caused by trauma, associated with mental disorders, or iatrogenically introduced 3 , 9 . Common symptoms of acute nasal foreign bodies include pain, airway obstruction, and epistaxis 3 .…”
Section: Discussionmentioning
confidence: 99%